2011
DOI: 10.1007/s00395-011-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidases in cardiovascular disease: insights from in vivo models and clinical studies

Abstract: NADPH oxidase family enzymes (or NOXs) are the major sources of reactive oxygen species (ROS) that are implicated in the pathophysiology of many cardiovascular diseases. These enzymes appear to be especially important in the modulation of redox-sensitive signalling pathways that underlie key cellular functions such as growth, differentiation, migration and proliferation. Seven distinct members of the family have been identified of which four (namely NOX1, 2, 4 and 5) may have cardiovascular functions. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 127 publications
(142 reference statements)
5
137
0
4
Order By: Relevance
“…The specificity of p47 phox ASON was confirmed by observations that the treatment did not affect Nox4 in RVLM ( Supplementary Fig. S4), the expression and activation of which do not require p47 phox subunit (54). We reported previously (27) that 7 days after transfection of the adenoviral vector encoding SOD1 or SOD2 (AdSOD1 or Ad-SOD2) into RVLM, the expression of cytosol SOD1 or mitochondrial SOD2 is upregulated, alongside reduced cytosolic and mitochondrial O 2 -level.…”
Section: Innovationsupporting
confidence: 70%
“…The specificity of p47 phox ASON was confirmed by observations that the treatment did not affect Nox4 in RVLM ( Supplementary Fig. S4), the expression and activation of which do not require p47 phox subunit (54). We reported previously (27) that 7 days after transfection of the adenoviral vector encoding SOD1 or SOD2 (AdSOD1 or Ad-SOD2) into RVLM, the expression of cytosol SOD1 or mitochondrial SOD2 is upregulated, alongside reduced cytosolic and mitochondrial O 2 -level.…”
Section: Innovationsupporting
confidence: 70%
“…Diabetes increases myocardial Nox4 expression, and its localization to the outer membrane of the mitochondria is significant (4,38,75). Unlike Nox1, Nox4 does not require p47 or p67 for activation, and biochemical studies suggest that it preferentially generates H 2 O 2 over superoxide (16,79,108). Block et al (4) demonstrated in mesangial cells that a siNOX4 probe abrogated glucose-induced increased superoxide generation.…”
Section: Discussionmentioning
confidence: 99%
“…In HF, it has been shown that increased amounts of superoxide are generated in mitochondria (69, 71, 103). In addition, NADPH oxidase (Nox) 2 and 4 are richly expressed in cardiomyocytes, and myocardial Nox activity has been shown to be increased in human HF (59,87,119). Stimuli relevant to the pathophysiology of HF (mechanical stretch, endothelin-1 and angiotensin II) are known to induce Nox activity (2,82).…”
Section: The Redox System Of the Heartmentioning
confidence: 99%